2007
DOI: 10.1111/j.1365-294x.2007.03151.x
|View full text |Cite
|
Sign up to set email alerts
|

Appraisal of the consequences of the DDT‐induced bottleneck on the level and geographic distribution of neutral genetic variation in Canadian peregrine falcons,Falco peregrinus

Abstract: Peregrine falcon populations underwent devastating declines in the mid-20th century due to the bioaccumulation of organochlorine contaminants, becoming essentially extirpated east of the Great Plains and significantly reduced elsewhere in North America. Extensive re-introduction programs and restrictions on pesticide use in Canada and the United States have returned many populations to predecline sizes. A proper population genetic appraisal of the consequences of this decline requires an appropriate context de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
50
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 61 publications
(56 citation statements)
references
References 103 publications
3
50
3
Order By: Relevance
“…Such 'ghost alleles' have subsequently been reported in several bottlenecked animal populations. By contrast, other studies have reported stable genetic diversity despite declines in population size [24][25][26]. For example, no obvious loss of genetic diversity was detected among Canadian peregrine falcons (Falco peregrinus) despite a DDT induced bottleneck [25].…”
Section: Nhc Samples In Conservation Geneticsmentioning
confidence: 45%
“…Such 'ghost alleles' have subsequently been reported in several bottlenecked animal populations. By contrast, other studies have reported stable genetic diversity despite declines in population size [24][25][26]. For example, no obvious loss of genetic diversity was detected among Canadian peregrine falcons (Falco peregrinus) despite a DDT induced bottleneck [25].…”
Section: Nhc Samples In Conservation Geneticsmentioning
confidence: 45%
“…All samples were kept frozen, and DNA extractions were performed using methods described elsewhere [34]. An additional 349 samples were obtained from the contemporary northern breeding distribution of peregrine falcons throughout Alaska, Canada and western Greenland, of which 168 samples were used in a previous study [35]. The samples collected from breeding territories were included in this study to verify the degree of population subdivision throughout their northern breeding distribution from which the Padre Island migrants likely originated.…”
Section: Methodsmentioning
confidence: 99%
“…While we expected to see a signal of declining genetic variation, other studies have also found mtDNA variation to be stable in species with declining populations (Brown et al 2007;Kuro-o et al 2010;Reding et al 2010). In these species, high levels of mtDNA variation were likely maintained because historical populations had high genetic variation or large effective population sizes prior to declines and because populations recovered or stabilized quickly once these species were managed.…”
Section: Discussionmentioning
confidence: 93%